Exploring Small Extracellular Vesicles for Precision Medicine in Prostate Cancer - Giulietti, Matteo; Santoni, Matteo; Cimadamore, Alessia; Carrozza, Francesco; Piva, Francesco; Cheng, Liang; Lopez-Beltran, Antonio; Scarpelli, Marina; Battelli, Nicola; Montironi, Rodolfo (Frontiers in Oncology, 2018)
Tumor microenvironment constitutes a complex network in which tumor cells communicate among them and with stromal and immune cells. It has been shown that cancer cells are able to exchange genetic materials through small extracellular vesicles (small EVs), an heterogeneous group of vesicles with different size and shape, cargo content and function. The importance to investigate populations of circulating extracellular vesicles would be of great importance as prostate cancer biomarkers. In several neoplasms as well as in prostate cancer (PCa), nanometer-sized extracellular vesicles of endosomal origin are implicated in supporting tumor growth and metastatic spread by both altering local stroma cells and creating a pro-tumor environment that favors the formation of pre-metastatic niches. Several techniques are applicable for the isolation and analysis of PCa-derived small EVs and are illustrated in this manuscript. Due to the high sensitivity and specificity of these techniques, small EVs have become ideal candidates for early diagnosis. Moreover, we discuss the role of small EVs during PCa carcinogenesis, as well as in modulating the development of drug-resistance to hormonal therapy and chemotherapy, thus underlining the potential of EVs-tailored strategies in prostate cancer patients.